LOX-1-Expressing Immature Neutrophils Identify Critically-Ill COVID-19 Patients at Risk of Thrombotic Complications - Combadière, Behazine; Adam, Lucille; Guillou, Noëlline; Quentric, Paul; Rosenbaum, Pierre; Dorgham, Karim; Bonduelle, Olivia; Parizot, Christophe; Sauce, Delphine; Mayaux, Julien; Luyt, Charles-Edouard; Boissonnas, Alexandre; et al. (Frontiers in Immunology, 2021)
Background: Lymphopenia and the neutrophil/lymphocyte ratio may have prognostic value in COVID-19 severity. Objective: We investigated neutrophil subsets and functions in blood and bronchoalveolar lavage (BAL) of COVID-19 patients on the basis of patients’ clinical characteristics. Methods: We used a multiparametric cytometry profiling based to mature and immature neutrophil markers in 146 critical or severe COVID-19 patients. Results: The Discovery study (38 patients, first pandemic wave) showed that 80% of ICU patients develop strong myelemia with CD10−CD64+ immature neutrophils (ImNs). Cellular profiling revealed three distinct neutrophil subsets expressing either the lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1), the interleukin-3 receptor alpha (CD123), or programmed death-ligand 1 (PD-L1) overrepresented in ICU patients compared to non-ICU patients. The proportion of LOX-1- or CD123-expressing ImNs is positively correlated with clinical severity, cytokine storm (IL-1b, IL-6, IL-8, TNFα), acute respiratory distress syndrome (ARDS), and thrombosis. BALs of patients with ARDS were highly enriched in LOX-1-expressing ImN subsets and in antimicrobial neutrophil factors. A validation study (118 patients, second pandemic wave) confirmed and strengthened the association of the proportion of ImN subsets with disease severity, invasive ventilation, and death. Only high proportions of LOX-1-expressing ImNs remained strongly associated with a high risk of severe thrombosis independently of the plasma antimicrobial neutrophil factors, suggesting an independent association of ImN markers with their functions. Conclusion : LOX-1-expressing ImNs may help identifying COVID-19 patients at high risk of severity and thrombosis complications.